Makna Jihad dalam al-Qur’an menurut Penafsiran Ibnu Katsir - Akmal Alna; Fatira Wahidah; Muh. Ikhsan; Muh. Syahrul Mubarak; Nurdin (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the meaning of jihad in the Qur'an according to the interpretation of Ibn Kathir. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the methodology of Ibn Kathir's interpretation, while the material object is the word jihad in the Qur'an. The results of the discussion of this study indicate that Ibn Kathir does not explore in depth the linguistic rules regarding the word jihad in the Qur'an but tends to use the source of the bi al-ma'tsur interpretation consistently as a reinforcement of the argument in his interpretation, he also does not explore the issue of jihad in the Qur'an. aspects of fiqh and socio-cultural aspects but when interpreting a verse about jihad will go straight to the core of the verse using a textual approach Ibn Kathir tends to interpret the verses of jihad in the Qur'an as a war against the enemy to defend Islam, he also emphasizes the urgency jihad and its virtues and features with concepts that are in line with Islamic law and in accordance with what is outlined by the Qur'an and also explained by the hadiths of the Prophet Muhammad. That is, the meaning of jihad in the Qur'an in Ibn Kathir's view does not only mean war, but the word jihad has a broad meaning. This study recommends that jihad must be interpreted comprehensively or thoroughly to avoid misunderstandings in the meaning of jihad.